SISTEM APLIKASI TAGIHAN AIR PADA PERUMAHAN PESONA SERPONG - Muhammad Taufiq Raihan; Martinus Lawolo; Muhammad Bagas R (Journal of Research and Publication Innovation, 2024)
Practical Work (KP) is a concrete manifestation of our commitment as students to provide a positive impact on the surrounding community. In order to meet the needs and demands of the times, this KP program will focus on introducing a water billing application system. Technology has become an important part in various aspects of life, including the management of utilities such as clean water. In many housing developments, water bill management is still done manually, which often causes problems such as recording errors, late payments, and difficulty accessing billing information. Practical Work Program (KP) with the title "WATER BILL APPLICATION SYSTEM IN PESONA SERPONG HOUSING" several stages and methods are carried out to achieve the goals that have been set. Training uses the application by paying attention to the procedures for using the water bill application that has been set for the housing. After the presentation of the material is complete, the public is asked to practice the explanation that has been delivered. Our hope is that in the future the public can easily access the application to view PDAM bills and can also use it for payment transactions.